ANALISIS IKATAN MOLEKUL PROTEIN (GUGUS FUNGSI C-N) PADA MISELIUM JAMUR TIRAM DENGAN METODE FOURIER TRANSFORM INFRA-RED (FTIR) - Abu Sonip; Erni Aprilina; Lusia Anita Br. Sagala; Maya Risanti; Mersi Kurniati; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Quality of oyster mushrooms depends on quality of oyster mushrooms seeds. Synthesis of oyster mushrooms seeds in this research consist of manufacture of potato dextrose agar (PDA), manufacture of pure seeds (F0), manufacture of scatter seeds (F1), and manufacture of planting seeds (F2). Sterilization of PDA has three variations, they are first level, second level, and third level with temperature 102 oC. Analysis protein (C-N) of micelium oyster mushroom with FTIR. Analysis of FTIR shows spring constant of C-N for pure seeds is 671 Nm-1, scatter seeds is 587 Nm-1, and pelanting seeds is 671 Nm-1. The bigger spring constant the more strong molekuler bonding , means big energy required to sever ties that molecule. Keywords : FTIR, micelium, molecular bonding, protein, spring constant